Exploring the Addition of Physician Identifiers to the California Hospital Discharge Data Set - Damberg, Cheryl L. (RAND Corporation, 2013)
To advance consideration of whether California should collect and release physician-identified data, RAND conducted a study to explore issues associated with requiring the inclusion of physician identifiers in the California hospital discharge data set and the potential use of physician-identified data by the state and/or release to others.